Studies on the genus Atriplex (Amaranthaceae) in Italy. V. Atriplex tornabenei - Iamonico, Duilio (Phytotaxa, 2013)
The typification of the name Atriplex tornabenei (a nomen novum pro A. arenaria) is discussed. An illustration by Cupani is designated as the lectotype, while a specimen from FI is designated as the epitype. Chorological and morphological notes in comparison with the related species A. rosea and A. tatarica are also provided. A nomenclatural change (Atriplex tornabenei subsp. pedunculata stat. nov.) is proposed.